Contextual Learning Approach and Performance Assessment in Mathematics Learning - Mahendra, I Wayan Eka (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2016)
This study aims to determine the effect of formative assessment and learning approach to the mathematics learning outcome after controlling the numerical aptitude. It was a quasi-experiment with a sample of 186 students obtained by using multistage random sampling technique with 2x2 factorial designs. The data were analyzed by ANCOVA. After controlling the numerical aptitude, the results are: the mathematics learning outcome of the students who followed a contextual approach was better than the ones who followed a conventional learning approach, the mathematics learning outcome of the students who were given a performance assessment was better than the ones who were given a conventional assessment, the interaction between the learning approach and formative assessment affected the students learning outcome for mathematics, the students who followed a contextual learning approach were more suitable to be given a performance assessment, whereas the ones who followed a conventional learning approach were more appropriate to be given a conventional assessment. Based on the research findings, junior high school teachers are suggested to improve their students learning outcome for mathematics. Then, teachers need to use a learning approach and formative assessment accurately and correctly.Â